Rebamipide: A novel agent in the treatment of recurrent aphthous ulcer and Behcet's syndrome - Mohan H Kudur; Manjunath Hulmani (Wolters Kluwer Medknow Publications, 2013)
Rebamipide is an amino acid analog of 2 (1H)-quinolinone. It is being introduced and used since 1980 for the treatment of peptic ulcer. Its therapeutic use in recurrent aphthous ulcer was not known. It acts by the decrease in oxygen radicals, increase in blood flow and production of protective prostaglandins in ulcer mucosa, which accelerates the process of healing. In this article, we focus on the pharmacodynamics, pharmacokinetics, side-effects and other therapeutic uses of Rebamipide. It will be a new and effective drug in the dermatologists' drug armamentarium for the treatment of aphthous ulcers and related diseases.